2012
DOI: 10.1371/journal.pone.0030755
|View full text |Cite
|
Sign up to set email alerts
|

Kinin-B2 Receptor Mediated Neuroprotection after NMDA Excitotoxicity Is Reversed in the Presence of Kinin-B1 Receptor Agonists

Abstract: BackgroundKinins, with bradykinin and des-Arg9-bradykinin being the most important ones, are pro-inflammatory peptides released after tissue injury including stroke. Although the actions of bradykinin are in general well characterized; it remains controversial whether the effects of bradykinin are beneficial or not. Kinin-B2 receptor activation participates in various physiological processes including hypotension, neurotransmission and neuronal differentiation. The bradykinin metabolite des-Arg9-bradykinin as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 36 publications
5
29
0
2
Order By: Relevance
“…The observed effects can be explained by the increased availability of Bk and subsequent activation of B2BkR, because they were reversed by pretreatment with HOE-140. Such neuroprotective features were recently described for an in vitro model of hippocampal neurons where Bk reversed apoptosis induced by NMDA-mediated excitotoxicity (62).…”
Section: Discussionmentioning
confidence: 86%
“…The observed effects can be explained by the increased availability of Bk and subsequent activation of B2BkR, because they were reversed by pretreatment with HOE-140. Such neuroprotective features were recently described for an in vitro model of hippocampal neurons where Bk reversed apoptosis induced by NMDA-mediated excitotoxicity (62).…”
Section: Discussionmentioning
confidence: 86%
“…PKA and PKC may phosphorylate NMDA or AMPA receptor subunits, changing the membrane traffic and their kinetic properties (voltage-dependent block, channel open time, burst behavior), triggering an increase in synaptic effectiveness (Kohno et al, 2008). Very recently, it was shown that B2R stimulation leads to neuroprotection after NMDA excitotoxicity in the CA1 area of rat hippocampal slices via phosphatidylinositol 3-kinase and not by MEK/MAPK signaling (Martins et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The same group described that a fluorescence live/dead confocal viability assay was consistent with the PSs assessment of neuronal damage after several pharmacological neuroprotective treatments [8]. PS have been successfully used to study the mechanism of neurotoxicity and neuroprotection [7, 9-13]. …”
Section: Introductionmentioning
confidence: 99%